The Effectiveness of a Combination of Lime (Citrus aurantifolia.), Lerak (Sapindus rarak) and Jasmine Flower (Jasminum nudiflorum) Extracts as and Environmentally Friendly Corrosion Inhibitor - Erna Noor Savitri; Putut Marwoto; Sunyoto Eko Nugroho (Postgraduate, University of Mataram, 2024)
Corrosion can also be defined as the forced destruction of metal by the surrounding medium which is usually a liquid (corrosive agent). Corrosion prevention processes can be carried out, including by coating the metal surface, cathodic protection, adding corrosion inhibitors and so on. Several types of inhibitors that have been widely used in industrial applications are synthetic chemical inhibitors. However, the compounds of inhibitors are environmentally unfriendly, toxic and expensive. To overcome this problem, it is necessary to develop an environmentally friendly alternative corrosion inhibitor or better known as a green inhibitor. This research aims to test the effectiveness of using a combination of lime (Citrus aurantifolia.), Lerak (Sapindus rarak) and jasmine flower (Jasminum nudiflorum) extracts as an environmentally friendly corrosion inhibitor. The results obtained were inhibitors in the form of a combination which were added to the corrosive medium HCl which could reduce the rate of aluminum corrosion. This research also shows that time and concentration influence the corrosion rate. A higher concentration (200 ppm) has a greater inhibitory power than a concentration of 100 ppm. The best inhibitory power is found in 200 ppm inhibitor with a soaking time of 20 minutes